The Treatment of Proximal Humeral Fracture in Adults - Burkhart, Klaus J (Deutscher Arzte Verlag, 2013)
BACKGROUND: The incidence of proximal humeral fractures lies between 105 and 342 per 100 000 persons per year. Around the world, this type of fracture remains a major challenge for treating surgeons. While non-displaced fractures can be managed conservatively, displaced ones are often treated surgically. METHODS: Selective literature review RESULTS: There are still no evidence-based schemes or guidelines for the treatment of proximal humeral fractures, and very few prospective randomized trials are available. The few that have been published recently show a trend in favor of conservative treatment, but they were carried out on small groups of patients and their findings are not directly generalizable. For younger patients, the goal of treatment is generally anatomical repositioning and osteosynthetic stabilization; for older patients, primary treatment with a prosthesis is a further option. Depending on the mode of treatment, complications can arise such as shoulder stiffness, necrosis of the humeral head, pain, infection, loss of reposition, and “cutting out.” CONCLUSION: Current evidence supports the individualized treatment of proximal humeral fractures. Treatment decisions must always be made jointly with the patient in consideration of his or her individual needs and characteristics. Particularly for elderly patients, the possibility of conservative treatment should be carefully considered. If conservative treatment is not possible, then the type of operation performed should also be a function of the surgeon’s individual skills and experience with particular types of implant.